Tamoxifen: The ideal post operative hormonal therapy to demote Ductal Carcinoma in Situ - Mirza, Maisa Tasnim (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.